O processo empreendedor na constituição da indicação geográfica Vale dos Vinhedos: uma análise sob a ótica do sistema de capitais - Radaelli, Adrieli Alves Pereira (My University, 2019)
The Vale dos Vinhedos region is the most important wine producer in Brazil, both in terms of tradition and production. It is located in the northeast of Rio Grande do Sul / Brazil and is made up of small rural properties, with the production of grapes and derivatives. In 1995, with the support of Embrapa (Brazilian Company of Agricultural Research), Aprovale (Association of Producers of the Vale dos Vinhedos) began a process for the constitution of a geographical indication for the wines produced in the region. Similar to the meaning of Terroir, the region has characteristics of soil and climate, as well as unique culture and savoir-faire that sustain a local structure of tangible and intangible values and capitals. There is a clear entrepreneurial process in the constitution of Vale dos Vinhedos. Previous studies have revealed the presence of capital tied to the value context of the region. Thus, the present study aims to analyze the process of constitution of the Vale dos Vinhedos Geographical Indication according to the theoretical perspective integrated between Entrepreneurial Process and Capital System. The thesis adopts the interpretative paradigm focused on the subject-object interaction, with a qualitative approach and using as a research strategy the unique case study, the Vale dos Vinhedos Geographical Indication. For the collection of data, we used as technique interviews narratives, semi-structured interviews and documentary analysis. The data analysis technique used was the content analysis and, for the organization and processing of the data, NVivo® software was used. Among the results presented, are the contextualization of the Vale dos Vinhedos as a Located Agri-Food System; the stages of the entrepreneurial process for the constitution of the Vale dos Vinhedos Geographical Indication; and the identification of the Capital System in the stages of the entrepreneurial process. The results allowed the construction of a framework of the entrepreneurial process sustained on a systemic basis of local capitals.
A região do Vale dos Vinhedos é uma produtora de vinhos finos importante do Brasil, tanto em termos de tradição quanto de produção. Está localizada no nordeste do Rio Grande do Sul/Brasil e é constituída de pequenas propriedades rurais, com produção de uvas e derivados. Em 1995, com o apoio da Embrapa (Empresa Brasileira de Pesquisas Agropecuárias), a Aprovale (Associação de Produtores do Vale dos Vinhedos) iniciou um processo para a constituição de uma indicação geográfica para os vinhos produzidos na região. Similar ao significado de terroir, a região possui características de solo e clima, bem como cultura própria e savoir-faire singulares que sustentam uma estrutura local de valores e capitais tangíveis e intangíveis. Há um claro processo empreendedor na constituição da IG Vale dos Vinhedos. Estudos anteriores revelaram a presença de capitais locais vinculados ao contexto de valor da região. Assim, o presente estudo tem como objetivo analisar o processo de constituição da Indicação Geográfica Vale dos Vinhedos de acordo com a perspectiva teórica integrada entre Processo Empreendedor e Sistema de Capitais. A tese adota o paradigma interpretativista centrada na interação sujeito-objeto, com abordagem qualitativa e utilizando como estratégia de pesquisa o estudo de caso único, a Indicação Geográfica Vale dos Vinhedos. Para a coleta dos dados, utilizou-se como técnica entrevistas narrativas, entrevistas semiestruturadas e análise documental. A técnica de análise dos dados utilizada foi a análise de conteúdo e, para a organização e tratamento dos dados, foi utilizado o software NVivo®. Entre os resultados apresentados, estão as etapas do processo empreendedor para a constituição da Indicação Geográfica Vale dos Vinhedos e a identificação de capitais locais nas etapas do processo empreendedor. Os resultados possibilitaram a construção de um framework do processo empreendedor sustentado numa base sistêmica dos capitais locais.
Keywords: Indicações geográficas (Marcas de origem) - Vale dos Vinhedos, Região (RS); Empreendedorismo; Capital (Economia); Geographical indications (Marks of origin) - Vale dos Vinhedos, Região (Brazil); Entrepreneurship; Capital (Economy)